PERFORMANCE STUDY OF HYDROGEN POWERED PETROL ENGINE (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Hydrogen powered vehicles have been in development for the past decade. While hydrogen fuel cells have been receiving the majority of the attention, they will not be ready for mass production for fifteen to twenty-five years. Hydrogen internal combustion engines may prove to be the most effective solution for the immediate future. This project explores the feasibility of making hydrogen internal combustion engines in mass produced vehicles. We researched the different methods for producing hydrogen, storing it in vehicles and converting traditional internal combustion to burn hydrogen instead of gasoline. Through this research, we investigated the advantages of hydrogen internal combustion engines over hydrogen fuel cells